New Phenolics from the Flowers of Punica granatum and Their In Vitro α-Glucosidase Inhibitory Activities - Yuan, Tao; Wan, Chunpeng; Ma, Hang; Seeram, Navindra P. (Planta Medica, 2013)
Two new phenolics, a 3-substituted coumarin, 7,8-dihydroxy-3-carboxymethylcoumarin-5-carboxylic acid (1), and a hydrolyzable tannin, namely punicatannin C (2), together with 10 known phenolics, were isolated from the flowers of pomegranate (Punica granatum). Their structures were determined on the basis of extensive spectroscopic analyses including HRESIMS, 1D and 2D NMR data. All the isolates were evaluated for in vitro α-glucosidase inhibitory activities.
Keywords: pomegranate; Punica granatum; Punicaceae; coumarin; hydrolyzable tannin; α-glucosidase inhibition